Can talent allocation drive transformation and upgrading of export trade through technological innovation under low-carbon background - Dan-Dan Kong; Ze-Hu Jin; Rong Wang (Technological and Economic Development of Economy)
Under the low-carbon background, regional talent allocation and transformation and upgrading of export trade are all important issues of common concern among academic circles in the stage of sustainable economic and environmental development. This paper explores talent allocation’s impact on the transformation and upgrading of export trade. Based on the results, the improvement in regional talent allocation level has significantly increased the percentage of regional general trade exports. It is conducive to the trans- formation and upgrading of export trade, and such an influence also shows the nonlinear characteristic of increasing “marginal effect”. This conclusion still stands after a series of robustness tests. According to the influencing mechanism test results, the technological innovation brought by the improvement in regional talent allocation level is an important transmission channel for such improvement to facilitate the transformation and upgrading of export trade. Based on the multi-dimensional analysis of the results of transformation and upgrading of export trade, regional talent allocation has significantly enhanced the complexity of exported technologies and actively promoted innovation among exporters. The research provides important inspiration for further promoting the structural reform of regional talent allocation and facilitating the transformation and upgrading of export trade patterns.